EDUKASI GEMAR IKAN: UPAYA PENINGKATAN KESADARAN DAN KEPEDULIAN SOSIAL MAHASISWA - Urip Tisngati; Tunjung Genarsih (LP2M STP Mataram, 2022)
Taking the momentum to commemorate the 93rd Youth Pledge Day in 2021, through community service programs, lecturers can help increase the role of students as agents of social change. Thus the purpose of this activity is to increase awareness, social awareness and the role of students in social life in the development process. Activities were carried out with the stages of preparation, implementation, preparation of activity reports, evaluations, and preparation of projected/planned activities as a follow-up. The method applied was a counseling. The results of the activity showed that: (1) the role of students in the life of society and the state can be done in the form of training, education, socialization, counseling, and social service; (2) Enjoyment education can be done in the form of peer tutor education about the benefits of fish and how to process fish. This PkM activity has an educational and social impact on the target group.